Flavonoids and biological activities of various extracts from Rosa sempervirens leaves - ŞEN, ALİ; BİTİŞ, LEYLA (TAYLOR & FRANCIS LTD, 2017)
Rosa sempervirens L. (Rosaceae) growing wildly in Turkey is used in folk medicine for various indications. Here, we report the isolation of four flavonoids and determination of the total phenolic and flavonoid contents and the antimicrobial and antioxidant activities of various extracts from R. sempervirens leaves. Antioxidant activity was determined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS). The total phenolic and flavonoid contents were determined using the Folin-Ciocalteu and AlCl3 methods, respectively. The antimicrobial activity was evaluated by the broth microdilution method against seven microbial species. The ethyl acetate extract (E) had significant antioxidant activity with half maximal inhibitory concentration (IC50) values of 3.96 in the DPPH and 2.92 mg/mL in the ABTS assay. The total phenolic (203.8 mg gallic acid equivalents/g extract) and total flavonoid (95.81 mg catechin equivalents/g extract) contents of the E extract were significantly higher as compared to other extracts. The E extract exhibited strong antimicrobial activity against Candida albicans with a minimum inhibitory concentration of 39 mg/mL. Quercetin 3-xyloside, quercitrin and hyperoside were isolated from the E extract and quercetin, from the chloroform extract, and quercetin and hyperoside were identified for the first time in this species. Quercitrin was found to be a major compound in the E extract. Antimicrobial activity of R. sempervirens was also reported for the first time. These results indicate that the E extract has significant antioxidant and antimicrobial activity, probably due to flavonoids as well as other phenolic compounds in the E extract, acting individually or in combination.
Keywords: Rosa sempervirens; antimicrobial activity; antioxidant activity; flavonoids; polyphenolic content; ANTIOXIDANT ACTIVITY; ANTIMICROBIAL ACTIVITY; ESSENTIAL OIL; ANTIBACTERIAL ACTIVITIES; PHENOLIC-COMPOUNDS; L.; PLANTS; POLYPHENOLS; CULTIVARS; PROFILES